PENGARUH CERITA WAYANG SUKURAGA TERHADAP PENDIDIKAN KARAKTER SISWA DI KELAS TINGGI SEKOLAH DASAR - Nurul Amalia; Iis Nurasiah; Dyah Lyesmaya; Yoesrina Novia Vini Syafitri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of the Sukuraga puppet story on the student’s character education in elementary schools. This study utilized a quasi-experimental type of quantitative approach. The design used in this research is the Nonequivalent Control Group Design. The subjects used in the study were 4 th -grade students of SDN Suryakencana CBM. The data collection tool in this study used a questionnaire using a Likert scale measurement consisting of 20 statements with the answers to statements including Always (SL), Often (SR), Sometimes (KK), Rarely (J), Never (TP). ) based on a checklist (√) on the attitude scale instrument grid. Based on the results of data processing pretest and posttest, with the calculation of the t-test carried out with the help of the IBM SPSS version software 26 with the results of planting character education using the Sukuraga puppet story, it obtained sig (2- tailed) 0.000 which is less than = 0.05. Based on the results from this calculation, it can be concluded that the story of the wayang Sukuraga affected the character education of students.